2006
DOI: 10.1124/jpet.106.106500
|View full text |Cite
|
Sign up to set email alerts
|

Y4 Receptors Mediate the Inhibitory Responses of Pancreatic Polypeptide in Human and Mouse Colon Mucosa

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…In addition to these findings, the rate of Y 4 receptor sequestration was found to be highly sensitive to agonist affinity and efficacy, i.e., full agonists induced a higher internalization rate than partial agonists (Parker et al , 2002a ;Tough et al , 2006 ). This is in agreement with the common mechanism of GPCR activation followed by sequestration, as described above, and underlines the fact that the endogenous Y 4 ligands generate two conformations, which are equally important for G protein and GRK/ Arr binding.…”
Section: Y 4 Receptorsupporting
confidence: 84%
See 3 more Smart Citations
“…In addition to these findings, the rate of Y 4 receptor sequestration was found to be highly sensitive to agonist affinity and efficacy, i.e., full agonists induced a higher internalization rate than partial agonists (Parker et al , 2002a ;Tough et al , 2006 ). This is in agreement with the common mechanism of GPCR activation followed by sequestration, as described above, and underlines the fact that the endogenous Y 4 ligands generate two conformations, which are equally important for G protein and GRK/ Arr binding.…”
Section: Y 4 Receptorsupporting
confidence: 84%
“…Initially, the hY 4 receptor was reported to be resistant to agonistpromoted desensitization and internalization when being expressed in Chinese hamster ovary cells (Voisin et al , 2000 ). In contrast, several other groups independently showed that the Y 4 receptor is rapidly internalized and subsequently transported back to the cell surface, most probably via the indirect recycling pathway (Parker et al , 2001(Parker et al , , 2002aTough et al , 2006 ;Bohme et al , 2008 ). The determined internalization and recycling rates were either comparable or slightly slower than those observed for the Y 1 receptor.…”
Section: Y 4 Receptormentioning
confidence: 82%
See 2 more Smart Citations
“…Physiologically, the Y 4 R is involved in the regulation of food intake (9), colonic anion transport (10), and adipose tissue and bone formation synergistically with Y 2 R (11). The Y 4 R sequence is one of the least conserved members of the NPYR family among different species, making it the fastest evolving functional member of the family (12).…”
mentioning
confidence: 99%